Synthesis and Characterization some Novel Heterocyclic Compounds of Pyrimidine and pyrazole from Chalcone derivatives - A Mosaa, Zaied (Al-Qadisiyah Journal of Pure Science, 2018)
In this article, several novel heterocyclic derivatives, for example, chalcone, Pyrazoles, and pyrimidine were synthesized by reaction 2,3-dichlorobenzaldehyde with paracetamol utilizing KOH as a catalyst to shape 3-(2, 3-Dichloro-phenyl)-N-(4-hydroxy-phenyl)-acrylamide (1).The compound (1) on interact with urea, Thiourea in the existence of KOH and methanol as a catalyst give 4-(2, 3-Dichloro-phenyl)-6-(4-hydroxy-phenylamino)-pyrimidin-2-ol (2) and 4-[6-(2, 3-Dichloro-phenyl)-2-mercapto-pyrimidin-4-ylamino]-phenol (3) individually. When compound (1) responding with hydrazine monohydrate in the existence of acetic acid as a stimulant substance it will give 4-[5-(2, 3-Dichloro-phenyl)-1H-pyrazol-3-ylamino]-phenol (4). All synthesized compounds have been distinguished by TLC, IR, 1H.NMR and 13C NMR spectroscopy.